Donde habitan los dioses: una aproximación a los apus más altos del Tawantinsuyu - Vitry Di Bello, Christian (Pontificia Universidad Católica del Perú, 2025)
Mountains have been worshipped by various cultures throughout the world, but documented case studies of ritual climbing are scarce. In the Andes, the Inca made offerings to more than 200 mountains from the fourteenth to the sixteenth centuries, 34 of which have an elevation of more than 6000 masl. This paper reviews Inca high mountain archaeology in these extreme summits, which hold the record for the highest-altitude archaeological evidence found throughout the world. The role of the Apus as tirakuna —living landscape beings with ritual and social agency— is explored through an analysis of material remains, ethnohistorical sources and recent approaches to Andean ontology. Major mountains like Llullaillaco, Aconcagua, and Mercedario are here studied incorporating technical, logistic and symbolic dimensions. This study presents an interpretation that reconstructs the planned, systematic and animate nature of these pre-Columbian practices, thus restating the very notion of mountaineering Andean-style.

Las montañas han sido objetos de culto en múltiples culturas del mundo, pero los casos documentados de ascensos rituales son escasos. En los Andes, durante los siglos XV y XVI, los incas realizaron ofrendas en más de 200 montañas, 34 de las cuales superan los 6000 metros de altura. Este artículo de revisión aborda la arqueología incaica de alta montaña en ese conjunto de cumbres extremas, donde se encuentran las evidencias arqueológicas más elevadas del planeta. A partir del análisis de vestigios materiales, fuentes etnohistóricas y enfoques recientes sobre la ontología andina, se examina el papel de los apus como tirakuna: entidades vivas del paisaje con agencia ritual y social. Montañas emblemáticas, como el Llullaillaco, el Aconcagua y el Mercedario, son analizadas integrando dimensiones técnicas, logísticas y simbólicas. Este estudio propone una lectura que restituye el carácter planificado, sistemático y animado de estas prácticas prehispánicas, replanteando la noción misma de montañismo en clave andina.
Where the gods dwell: an approach to the highest-altitude apus in Tawantinsuyu
Keywords: High mountain archaeology; Sacred mountains; Ritual landscapes; Tawantinsuyu; Apus; Pre-Columbian mountaineering; Arqueología de alta montaña; Montañas sagradas; Paisajes rituales; Tawantinsuyu; Apus; Montañismo prehispánico; https://purl.org/pe-repo/ocde/ford#6.01.02